2016
DOI: 10.1002/per.2068
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Other Lifelong Influences on Older–Age Health and Wellbeing: Preliminary Findings in Two Scottish Samples

Abstract: Recent observations that personality traits are related to later‐life health and wellbeing have inspired considerable interest in exploring the mechanisms involved. Other factors, such as cognitive ability and education, also show longitudinal influences on health and wellbeing, but it is not yet clear how all these early‐life factors together contribute to later‐life health and wellbeing. In this preliminary study, we assessed hypothesised relations among these variables across the life course, using structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 99 publications
(180 reference statements)
4
19
0
Order By: Relevance
“…To put these findings into perspective and further illustrate the role of mortality-related processes for late-life development, we also conducted a follow-up analysis using chronological age (centered at 70 years) rather than time-to-death as the underlying time-metric. In the model of age-related processes, we found a pattern of results more similar to previous reports focusing on midlife or individuals in their 60s and 70s (e.g., Harris et al, 2016;Tauber et al, 2016) showing slightly steeper decreases (γ = -0.07). Interestingly, associations between neuroticism and extraversion with rates of well-being change were not significant in the age-based model.…”
Section: The Role Of Personality For Late-life Well-being Trajectoriessupporting
confidence: 88%
“…To put these findings into perspective and further illustrate the role of mortality-related processes for late-life development, we also conducted a follow-up analysis using chronological age (centered at 70 years) rather than time-to-death as the underlying time-metric. In the model of age-related processes, we found a pattern of results more similar to previous reports focusing on midlife or individuals in their 60s and 70s (e.g., Harris et al, 2016;Tauber et al, 2016) showing slightly steeper decreases (γ = -0.07). Interestingly, associations between neuroticism and extraversion with rates of well-being change were not significant in the age-based model.…”
Section: The Role Of Personality For Late-life Well-being Trajectoriessupporting
confidence: 88%
“…In terms of a simple overall snapshot, recent global studies indicate around 60% of youth are happy with their lives, showing much room for improvement ( Helliwell et al, 2016 ; Broadbent et al, 2017 ). Meta-analytic studies complement these findings, indicating happiness is predicted by educational attainment and cognitive ability ( Witter et al, 1984 ; Harris et al, 2016 ), socio-economic status and various forms of social support ( Pinquart and Sörensen, 2000 ), physical health ( Veenhoven, 2008 ), personality traits ( Harris et al, 2016 ) and a connectedness with nature ( Capaldi et al, 2014 ). In the current study we explore the role of parenting, specifically SBP, in predicting teen happiness.…”
Section: Introductionmentioning
confidence: 83%
“…Well-being, defined as a good or satisfactory condition of existence, quality of life, and health are closely related, and this relationship is important at older ages [9,10]. Wellbeing is positively associated with quality of life and physical health benefits, including a decreased risk for disease, speedier disease recovery, and increased longevity [6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Well-being, defined as a good or satisfactory condition of existence, quality of life, and health are closely related, and this relationship is important at older ages [9,10]. Wellbeing is positively associated with quality of life and physical health benefits, including a decreased risk for disease, speedier disease recovery, and increased longevity [6][7][8][9][10][11][12][13]. In parallel, it has been found that art-based activities are positively associated with numerous aspects of individuals' physical health, like a better immune system response and slower disease progression, with these effects being related to well-being improvement [3,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%